2018
DOI: 10.1016/j.foodchem.2018.05.126
|View full text |Cite
|
Sign up to set email alerts
|

Influence of milling type on tef injera quality

Abstract: Injera is an Ethiopian flat bread that is mostly made from tef flour. Injera making on an industrial scale holds a significant economic and social interest but requires a thorough study of how the process variables affect the product quality. The aim of this work was to investigate the effects of mill type (hammer, disc, and blade) on injera sensory quality and starch digestibility. The application of software for the determination of injera quality descriptors and its comparison with visual human eye evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Before milling, tef grain was cleaned by sifting. The kneading conditions (time/speed) ( Table 1) were used based on preliminary assessment of injera exporters, kneading machine capacity, and other works on bread dough kneading; similarly the ratio of water to fermented dough for absit preparation was based on previous work (Assefa et al, 2018) and traditional practices. Based on the sensory results, Kneading # 1, with shorter kneading time and slower kneading speed, had moderate overall injera acceptability; #5, with moderate kneading time and moderate speed, had the highest injera acceptability; and #9, with longer kneading time and fastest kneading speed, had the lowest injera acceptability; they were selected for starch hydrolysis, flavonoids, total phenolics, phytate and tannins analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before milling, tef grain was cleaned by sifting. The kneading conditions (time/speed) ( Table 1) were used based on preliminary assessment of injera exporters, kneading machine capacity, and other works on bread dough kneading; similarly the ratio of water to fermented dough for absit preparation was based on previous work (Assefa et al, 2018) and traditional practices. Based on the sensory results, Kneading # 1, with shorter kneading time and slower kneading speed, had moderate overall injera acceptability; #5, with moderate kneading time and moderate speed, had the highest injera acceptability; and #9, with longer kneading time and fastest kneading speed, had the lowest injera acceptability; they were selected for starch hydrolysis, flavonoids, total phenolics, phytate and tannins analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Absit variables Kneading treatment Time (min) Speed (speed) Absit treatment Fermented dough (ml) Water (ml) 1 1 1 1 100 100 2 1 6 2 100 300 3 1 12 3 100 900 4 3 1 4 300 100 5 3 6 5 300 300 6 3 12 6 300 900 7 7 1 7 0 100 8 7 6 8 0 300 9 7 12 9 0 900 appearance, texture and taste. According to Assefa et al (2018), a normal and typical injera is round, soft, spongy and resilient, about 6 mm thick with uniformly spaced honeycomb-like ""eyes"" on the top. The fermentation of injera starts by adding water to tef flour and mixing or kneading it with a starter (backslopped culture) called ersho.…”
Section: Kneading Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the effect of different milling processes on the resulting flour quality and characteristics are also scarce. Assefa et al (2018) experimented on the resulting qualities of injera bread made from teff flour that was milled using a hammer mill, stone-disk mill and blade mill. They reported that the injera made from the flour from disk mill has the highest overall acceptability.…”
Section: Teff Processing and Future Applicationsmentioning
confidence: 99%
“…This explains why the disk mill is often used for milling teff in Ethiopia. Moreover, the use of disk mill resulted in the smallest flour particle size and high starch damage, while the blade mill resulted in the largest particle size (Assefa et al, 2018). Studies on the adoption of different milling techniques like roller milling and attrition milling may be conducted in the future since the quality of the final product is significantly affected by the method of milling (Kihlberg et al, 2004).…”
Section: Teff Processing and Future Applicationsmentioning
confidence: 99%